Effect of heat ameliorative measures on microclimate, physiological, blood biochemical parameters and milk production in lactating Surti buffaloes - CHAUDHARY, SANDHYA S; SINGH, RANA RANJEET; SINGH, V K; MANAT, T D; KHARADI, V B; SORATHIYA, L M (The Indian Journal of Animal Sciences, 2019)
The present investigation was carried out to evaluate the effect of heat ameliorative measures (fans, foggers, green agro shadenet) on physiological, haematological, biochemical and milk production parameters in Surti buffaloes. Lactating Surti buffaloes (36) were equally divided into two groups and kept in two sheds. Group I animals were housed in a shed without any modification while Group II animals housed in a shed fitted with fans and foggers inside the shed and roof top white washed with microfine lime and open paddock was covered with green shade net and foggers were fitted. There were significant differences in the THI values of both inside and outside of the sheds at majority of periods during the hot-dry season. The floor and roof temperature of control shed at almost all-time intervals was significantly higher than the floor temperature of treatment shed. Significant difference in rectal temperature was observed at 14 and 28 days while respiration rate was significantly lower in animals of treatment shed. In treatment group, total erythrocyte count and haematocrit was significantly low at day 21 and mean platelet volume was significantly high at day 42. Significantly high levels of cholesterol, chloride and sodium at day 21 and glucose, protein, triglyceride, GSH, TAS and sodium at day 42 were observed in treatment group. Weekly milk yield (kg) during hot-dry season was significantly higher for treatment group than control group at 3rd, 4th and 5th weeks of the experiment. Evening milk yield of treatment group was significantly higher than the control and the cumulative milk yield (for 42 days) was also significantly higher for treatment group than control group (180.08 vs.150.80 kg). It can be concluded that microclimate modifications help in reducing heat stress and has beneficial effect on physiological responses, blood biochemical parameters and total milk production in lactating Surti buffaloes during hot dry season.